Ballistic projectile maxillofacial injuries in the context of human rights violations in Chile: A 5-case series. - Jesús Silva; Denisse Lagos-Tissie; Marcos Faundes; Fiorella Betanzo; Ángela López (Torture)
Introduction: On 18 October 2019, Chile experienced a wave of civil protests driven by social demands, which continued for several months across the country. The response by law enforcement and armed forces resulted in injuries caused by ballistic projectiles, some of which affected the maxillofacial region. Materials and Methods: This is a multiple case report study analysing five forensic reports prepared by forensic odontologists from the Medicolegal Service of the Valparaíso region, Chile. Results: Various injuries were observed, including fractured teeth, scars, paraesthesia, and embedded ballistic projectiles. Discussion: The injuries are often permanent, compromising functionality and causing aesthetic and functional damage. Lead poisoning should be considered in cases where projectiles remain lodged in soft tissues.